2019
DOI: 10.18438/eblip29509
|View full text |Cite
|
Sign up to set email alerts
|

Using Ethnographic Methods to Explore How International Business Students Approach Their Academic Assignments and Their Experiences of the Spaces They Use for Studying

Abstract: Objective -Understanding students' approaches to studying and their experiences of library spaces and other learning spaces are central to developing library spaces, policies, resources and support services that fit with and meet students' evolving needs. The aim of the research was to explore how international students approach academic assignments and how they experience the spaces they use for studying to determine what constituted enablers or barriers to study. The paper focuses on how the two ethnographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Library staff at the university had previously used UX techniques in related research with international students, also identified as low library users (Jensen et al, 2019). The objectives for this research were similar enough that it was thought the same UX methods would be suitable.…”
Section: Ux Techniquesmentioning
confidence: 99%
“…Library staff at the university had previously used UX techniques in related research with international students, also identified as low library users (Jensen et al, 2019). The objectives for this research were similar enough that it was thought the same UX methods would be suitable.…”
Section: Ux Techniquesmentioning
confidence: 99%